Metallic Ratios and Pascal’s Triangle : Triads of Metallic Means in the Pascal’s Triangle (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
This paper introduces the close correspondence between Pascal’s Triangle and the recently published mathematical formulae those provide the precise relations between different Metallic Ratios. The precise correlations between various Metallic Means can be substantiated with Pascal’s Triangle, as described herein.